Data from: Accelerometers can measure total and activity-specific energy expenditure in free-ranging marine mammals only if linked to time-activity budgets - Jeanniard-Du-Dot, Tiphaine; Guinet, Christophe; Arnould, John P. Y.; Speakman, John R.; Trites, Andrew W.; Arnould, John P.Y. (Dryad, 2017)
Dryad version number: 1 Version status: submitted Dryad curation status: Published Sharing link: https://datadryad.org/stash/share/h4srE2l8uSZYxl3JXhWDLNbXHRhwyiswdFoyWiYPzlg Storage size: 3923822293 Visibility: public Usage notes Northern fur seals data Data was collected on northern fur seal females during the breeding season on St Paul island, Bering Sea, Alaska from a daily Diary tag from Wildlife Computers. Column headings include "Date", "Time","Depth", "External Temperature", "int mX", "int mY", "int mZ", "int aX", "int aY", "int aZ", "Light Level", "Velocity", "Wet/Dry", "Wet/Dry", "Hour", "Battery Voltage", "Protocol". int mX, Y, Z refer to magnetic field recorded on the 3 body axes, and int aX, Y, Z to the acceleration recorded on the same axes. Northern_fur_seals_data.zip Antarctic fur seal data Data was collected on Antarctic fur seal females during the breeding season on Kerguelen Island, Southern Ocean on The Pointe Suzanne colony from a Daily Diary tag from Wildlife Computers. Column headings include "Date", "Time", "Depth", "Temperature", "aX", "aY", "aZ", "Light", "Velocity", "WetDry", "WetDrytxt". aX, Y, Z refer to the acceleration recorded on the 3 body axes. Antarctic_fur_seal_data.zip Abstract Energy expenditure is an important component of foraging ecology, but is extremely difficult to estimate in free-ranging animals and depends on how animals partition their time between different activities during foraging. Acceleration data have emerged as a new way to determine energy expenditure at a fine scale but this needs to be tested and validated in wild animals. This study investigated whether vectorial dynamic body acceleration (VeDBA) could accurately predict the energy expended by marine predators during a full foraging trip. We also aimed to determine whether the accuracy of predictions of energy expenditure derived from acceleration increased when partitioned by different types of at-sea activities (i.e. diving, transiting, resting and surface activities). To do so, we equipped 20 ...